DILEMA ETIKA PROFESI GURU DI ERA DIGITAL DALAM MENGHADAPI DISRUPSI AI YANG MENGANCAM KEJUJURAN AKADEMIK DAN INTEGRITAS PENDIDIKAN - Septia Rosada; Indah Rahmayani; Nur Anisa; Mafaza, Vina; Muhlisin , Muhlisin; Abul Mafaakhir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of artificial intelligence (AI) in education has brought significant changes, but has also given rise to ethical dilemmas for the teaching profession, particularly regarding academic honesty and educator integrity. This study aims to analyze the forms of ethical dilemmas faced by teachers in the digital era, examine the impact of AI use on academic honesty, and identify strategies that can be implemented to maintain professional integrity in an adaptive and responsible manner. The method used is a qualitative approach with a literature study, through an analysis of various scientific journals and relevant sources from the past five years related to educational ethics and the use of AI. The results show that the use of AI has the potential to increase learning efficiency, but also triggers the risk of plagiarism, cognitive dependency, and a decline in students' critical thinking skills. Furthermore, a gap in digital ethics literacy among teachers was found, resulting in weak oversight and enforcement of academic integrity. Therefore, it is necessary to strengthen AI ethics literacy, improve teachers' professional competence, and develop adaptive education policies to ensure that technology is used wisely without neglecting the values of academic honesty and responsibility.